Measuring the response to simulated fixture congestion in soccer. Issue 4 (1st October 2020) - Tofari, Paul J.; Kemp, Justin G.; Cormack, Stuart J.
ABSTRACT: Introduction: Competitive soccer results in acute physiological and perceptual disturbances lasting up to 96-h, yet multiple games are often played with 72-h rest. Contextual factors influence match activities, impacting the assessment of post-match responses. We assessed the within- and post-match responses to two self-paced simulations (SIM1 and SIM2) in a 72-h period. Method: Eleven male team-sport athletes attended eight consecutive testing sessions after familiarisation. Assessments occurred at pre-, half-time, post- and 2 h post-SIM1, and daily up to four-days after SIM2. Statistics included effect size ± 90% CL comparisons to pre-SIM1 and regression analysis. Results: At half time there was reduced voluntary activation (SIM1: −1.52 ± 1.41 and SIM2: −0.50 ± 0.58) and potentiated twitch torque (SIM1: −0.50 ± 0.37 and SIM2: −0.31 ± 0.37), suggesting central and peripheral fatigue, respectively. The difference in activity profiles between simulations was unclear. Both simulations resulted in acute physiological and perceptual decrements, similar to published data from competitive matches. Higher strength was associated with reduced soreness and fatigue at all time points (range: r = 0.27 to 0.69) and lower peripheral fatigue. vV.O2peak was negatively associated with CK (range: r = −0.28 to −0.70). Conclusion: 72-h recovery is sufficient to maintain activity between simulations. Lower-body strength and aerobic capacity displayed protective effects against post-simulation decrements.